Infiltrating Kaposi sarcoma presenting as acute kidney injury: An unexpected consequence of deliberate hepatitis C–positive organ transplantation. Issue 2 (22nd October 2020) - Story, Maria T.; Sanders, M. Lee; Bashir, Amani A.; Longo, Jude M.; Abel, Stacy L.; Dollard, Sheila C.; Grodstein, Elliot I.; Thomas, Christie P.; Katz, Daniel A.
Abstract: Kaposi sarcoma (KS) following kidney transplantation can result from recipient reactivation of latent human herpesvirus 8 (HHV‐8) infection or activation of donor‐acquired HHV‐8 infection. Post‐transplant KS typically manifests with cutaneous pathology, but rare cases of renal allograft involvement have been reported. We describe two cases of donor‐derived HHV‐8 infection in two hepatitis C (HCV) viremia‐negative transplant recipients who each received a kidney from a donor with HCV viremia. One recipient did not develop KS while the other presented with acute kidney injury caused by extensive KS infiltration of the renal parenchyma and metastatic disease. This report reviews the literature for cases of KS involving the renal allograft and highlights an unexpected consequence of deliberate HCV‐positive organ transplantation.